Online korean skincare decision support system - Wahid, Norfaradilla; Low, Zhen Ying; Kasim, Shahreen; Hafit, Hanayanti (Penerbit UTHM, 2017)
Despite the explosive growth of electronic commerce and the rapidly increasing number of consumers who use interactive media for pre-purchase information search and online shopping, very little is known about how consumers make purchase decisions in such settings. One desirable form of interactivity from a consumer perspective is the implementation of sophisticated tools to assist shoppers in their purchase decisions by customizing the electronic shopping environment to their individual preferences.